2022
DOI: 10.3389/fpsyg.2022.874181
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of e-Learning Systems on Motivating Students and Enhancing Their Outcomes During COVID-19: A Mixed-Method Approach

Abstract: e-Learning is a key strategy in the course of higher education to improve the results of the educational process and stimulate student motivation. The COVID-19 pandemic imposed on Algerian universities to adopt e-Learning systems to search for effectiveness and efficiency of academic approaches. This paper seeks to remedy these problems by analyzing the impact of e-Learning systems on student motivation and outcomes. A mixed-method approach was used in the data analysis. We conducted the study as a survey, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 74 publications
0
11
0
3
Order By: Relevance
“…Some studies focus on the effectiveness of desktop systems in assisting students. Yahiaoui et al [69] analyzed the impact of desktop e-learning systems on student motivation and performance and found that both students' motivation and performance were significantly influenced by desktop e-learning systems. Perez et al [48] evaluated the NEO learning management system and found that the system met the international quality standards for management systems.…”
Section: Effectiveness Evaluation Of Learning Systemsmentioning
confidence: 99%
“…Some studies focus on the effectiveness of desktop systems in assisting students. Yahiaoui et al [69] analyzed the impact of desktop e-learning systems on student motivation and performance and found that both students' motivation and performance were significantly influenced by desktop e-learning systems. Perez et al [48] evaluated the NEO learning management system and found that the system met the international quality standards for management systems.…”
Section: Effectiveness Evaluation Of Learning Systemsmentioning
confidence: 99%
“…ELearning has become an inevitable technique for institutions of higher learning, imposing alternate learning and teaching process configurations focused on: blended learning, distance learning, online courses, and smart learning. [35]. because the majority of research in the literature proposes novel E-learning methodologies to improve learning outcomes, it is critical to investigate the effects of students' gender on technical abilities.…”
Section: Concept Of the E-learning Processmentioning
confidence: 99%
“…Yahiaoui, [15] study indicated that e-Learning systems, encompassing technical and electronic requirements, personal requirements, perceived value, and credibility of e-Learning, exert a significant influence on student motivation (Attention, Relevance, Confidence, and Satisfaction) as well as student outcomes (knowledge, skills, and attitudes). In the given context, Barba et al [16] have demonstrated a significant correlation between learner motivation and engagement in online environments.…”
Section: Review Of Related Literaturementioning
confidence: 99%